The Degree to Which Secondary School Principals in Zarqa Governorate Practice Servant Leadership and its Relationship to Organizational Culture from the Point of View of Teachers - Awwad, Hidaya Khaled (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree to which secondary school principals in Zarqa Governorate practice servant leadership and its relationship to organizational culture from the teachers' point of view. The results of the study showed a high degree in the practice of servant leadership by school principals in Zarqa Governorate from the teachers’ point of view, with a total average of 3.88 out of 5. As for the sub-dimensions, the technical skills score was on the highest mean (3.97), then the teachers’ concern with an average of 3.93) and thirdly, teacher development with an average of (3.87), fourthly, empowerment with an average of (3.86) and finally altruism with an average of (3.79), all with a grade (high), and there is a high degree in the level of organizational culture in secondary schools in Zarqa Governorate from the teachers’ point of view, with a total average of (3.67 out of 5). As for the sub-dimensions, organizational values came first; With an average of (3.97), then future expectations with an average of (3.69), both with a rating (high), and thirdly, organizational norms with an average of (3.55), and finally, organizational beliefs with an average of (3.44), both with a rating (medium), and there are no differences in the opinions of teachers about the degree of practice of secondary school principals in Zarqa governorate of servant leadership or the level of organizational culture from the teachers’ point of view according to the variables (gender, age, educational qualification, type of education), and the correlation coefficients between the level of servant leadership and the level of organizational culture among teachers in Zarqa governorate (0.98), and they indicate a strong and direct relationship And statistically significant at (α≥0.05), and based on the results of the study, the researcher recommended: It is necessary to present seminars, lectures and training programs for teachers in schools in general and in the schools of the Directorate of Education in Zarqa in particular, on modern methods of leadership, including servant leadership, and on modern administrative methods such as organizational culture, Spreading the culture of servant leadership, its dimensions and ethics among school leaders through school leadership supervisors and holding courses, programmers, workshops and educational meetings in the Ministry of Education To increase and improve their performance within the school.
Keywords: degree of practice; servant leadership; relationship; organizational culture; secondary school principals; Zarqa Governorate